ANALISIS DAYA DUKUNG LAHAN PERTANIAN PANGAN DI KABUPATEN TANAH DATAR TAHUN 2002-2018 - Elma liana; iswandi U (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
The purpose of this research is to know the dynamics of changes in paddy fields and carrying capacity of agricultural land in Tanah Datar District in 2002 - 2018. It is a quantitative descriptive study. Using the supervised classification method, and the formula for comparing the area of harvest of food crops per capita with the area of land for food self-sufficiency. Results: 1) The area of paddy fields in the Tanah Datar districts in 2002 - 2018 was reduced by 4189 Ha. 2) Class I self-sufficiency areas in Tanah Datar District were eight sub-districts in 2002, namely Batipuh, Batipuh Selatan, , Pariangan, Tanjung Emas, Lintau Buo, Salimpaung and Tajung Baru Districts. In 2010 there were 3 additional districts of Lintau Buo Utara, Sugayang and Padang Ganting, in 2018 an increase in 1 Rambatan District. Regional food self-sufficiency classes II, namely Lintau Buo District, Lima Kaum and X Koto.